Effects of grape pomace in growing lamb diets compared with vitamin E and grape seed extract on meat shelf life. (June 2016) - Guerra-Rivas, C.; Vieira, C.; Rubio, B.; Martínez, B.; Gallardo, B.; Mantecón, A.R.; Lavín, P.; Manso, T.
Abstract: The effect of dietary treatment (CTRL, control; VIT-E, 500 mg kg − 1 vitamin E; GSE, 50 mg grape seed extract kg − 1 ; GP-5, 5% dried red grape pomace kg − 1 ) on shelf life of lamb meat was studied. After slaughter (27 kg LBW), m. longissimus thoracis et lumborum was sliced, packaged under modified atmosphere (80:20%/O2 :CO2 ) and stored in retail conditions for 14 days. At each sampling day (0, 4, 7, 11, 14), microbiological, physico-chemical and sensory characteristics were analysed. Meat from VIT-E presented lower microbial counts than CTRL, GSE and GP-5, without differences between polyphenol treatments (GSE and GP-5) and CTRL. Vitamin E reduced meat discoloration and lipid oxidation (TBARS values) from day 7 with respect to the other treatments. Although not significant, an improvement in TBARS values of about 20% was observed for GSE and GP-5, compared with CTRL, from day 7 of storage. VIT-E dietary treatment was more effective in preventing sensory spoilage than the other treatments. Highlights: The effect of grape pomace on lamb meat shelf life was studied. Meat from vitamin E lambs showed lower microbial counts than lambs fed grape pomace. Vitamin E was more effective in preventing sensory spoilage than grape pomace. The use of grape pomace decreased lipid oxidation by about 20%.